2013
DOI: 10.4172/2157-7579.1000135
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Feeding Yeast Culture on Milk Yield, Milk Components, and Blood Components in Algerian Dairy Herds

Abstract: The main objective of this study was to estimate the effect of supplementation with Saccharomyces cerevisiae (BIOSAF ® SC 47), on body condition score, milk production and some biochemical parameters in peripartum dairy cows. The experiment was conducted during 14 days before parturition to 45 days postpartum (20 milking). Holstein cows (16 primiparous and 4 multiparous) were randomly divided into two groups (n=10); the groups were fed with same diet: One group received, Saccharomyces cerevisiae. Milk producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The results of the study coincide with those of other authors (Poppy et al, 2012;Maamouri et al, 2014;Para et al, 2018) on the positive effect of combined probiotic feed additives with yeast on the milk productivity of cows. As noted in the literature review, yeast supplements increase milk yield in the first half of lactation, and milk fat content increases at the end of lactation, which allows using them during different lactation periods (Ayad et al, 2013;Bakr et al, 2015;Sun et al, 2021). However, the effectiveness of the application varies depending on the diet and strain, which is confirmed by the results obtained.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The results of the study coincide with those of other authors (Poppy et al, 2012;Maamouri et al, 2014;Para et al, 2018) on the positive effect of combined probiotic feed additives with yeast on the milk productivity of cows. As noted in the literature review, yeast supplements increase milk yield in the first half of lactation, and milk fat content increases at the end of lactation, which allows using them during different lactation periods (Ayad et al, 2013;Bakr et al, 2015;Sun et al, 2021). However, the effectiveness of the application varies depending on the diet and strain, which is confirmed by the results obtained.…”
Section: Resultssupporting
confidence: 63%
“…Feeding cows with S. cerevisiae included leads to an increase in milk yield (by 1.18 kg/day), milk fat, and protein during the first 70 days of lactation (Poppy et al, 2012). According to other studies, the use of yeast from 73 days of lactation lasting 70 days led to an increase in milk yield by 1.36 litres (Sun et al, 2021), and after 42 days of feeding yeast to cows, milk yield increased by 23% and the peak lactation lengthened by 1 week (Ayad et al, 2013). Other authors also report an increase in milk yield and a decrease in the percentage of protein in milk (Bakr et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 88%
“…We note from some research works the use of yeast as fortifying in animal feed, in particular, dairy cows using Saccharomyces cerevisiae to improve milk production [39][40][41]. So far we cannot consider this as community adoption, but it will be in the future due to the increasing need and cost of feed.…”
Section: Other Ethnobiological Casesmentioning
confidence: 99%
“…An Acad Bras Cienc (2020) 92(3) e20191140 2 | 8 composition for live yeast culture consists of dry matter (DM) 93%, crude protein (CP) 44.50%, ether extract (EE) 1.10%, ash 3.50%, crude fiber (CF) 2.75%, metabolizable energy (ME) 1990 Kcal/ Kg (Küçükersan et al 2009). Several studies has been reported with positive influence of Saccharomyces cerevisiae on DM intake (Titi et al 2008), nutrient digestibility (Obeidat et al 2018, Ullah et al 2017, live weight gain (Yalcin et al 2011), feed conversion ratio (Lesmeister et al 2004), ruminal parameters (rumen pH, ruminal ammonia concentration), milk production and milk composition (Ayad et al 2013). Therefore, it can be a better replacement of conventional protein sources (Sharif et al 2018).…”
Section: Saccharomyces Cerevisiae Ferments Rice Polishingmentioning
confidence: 99%